Diminished gray matter in the hippocampus of cannabis users: Possible protective effects of cannabidiol - Demirakça, Traute; Sartorius, Alexander; Ende, Gabriele; Meyer, Nadja; Welzel, Helga; Skopp, Gisela; Mann, Karl; Hermann, Derik (Drug and alcohol dependence, 2011)
Background - Chronic cannabis use has been associated with memory deficits and a volume reduction of the hippocampus, but none of the studies accounted for different effects of tetrahydrocannabinol (THC) and cannabidiol (CBD). - Methods - Using a voxel based morphometry approach optimized for small subcortical structures (DARTEL) gray matter (GM) concentration and volume of the hippocampus were measured in 11 chronic recreational cannabis users and 13 healthy controls, and correlated with THC and CBD from hair analyses. GM volume was calculated by modulating VBM using Jacobian determinants derived from the spatial normalization. - Results - Cannabis users showed lower GM volume located in a cluster of the right anterior hippocampus (Puncorr=0.002; effect size Cohen's d=1.34). In a regression analysis an inverse correlation of the ratio THC/CBD with the volume of the right hippocampus (Puncorr p<0.001, Cohen's d=3.43) was observed. Furthermore Cannabidiol correlated positively with GM concentration (unmodulated VBM data), but not with GM volume (modulated VBM) in the bilateral hippocampus (P=0.03 after correction for hippocampal volume; left hippocampus Cohen's d=4.37 and right hippocampus 4.65). - Conclusions - Lower volume in the right hippocampus in chronic cannabis users was corroborated. Higher THC and lower CBD was associated with this volume reduction indicating neurotoxic effects of THC and neuroprotective effects of CBD. This confirms existing preclinical and clinical results. As a possible mechanism the influence of cannabinoids on hippocampal neurogenesis is suggested.
Available online 2 November 2010
Gesehen am 06.05.2022